(untitled) (Research, Society and Development, 2020)
The veterinarian role in promoting human health has been often unknown to the Brazilian population, due to the belief that this profession is dedicated only to the areas of the clinic and surgery of small and large animals. This work aimed to evaluate, through a questionnaire, the population perception, of Córrego Rico District, São Paulo State, about the veterinarian role, and verify their knowledge about rabies, leptospirosis, leishmaniasis, dengue fever, and toxoplasmosis. According to the obtained results, from 141 respondents, 92.9% claimed to know the veterinarian’s work activities and when asked about what would they be, 96.9% mentioned small/large animal clinic. Only 3.1% of the respondents associated with their performance at the public health, pointing out the work at Zoonoses Surveillance Units, in Health Surveillance System and Dengue Fever Control Programmes. In regards to urban zoonoses, when asked if they knew what rabies means, 85.8% of the respondents stated that they knew, and when inquired about leishmaniasis, toxoplasmosis, leptospirosis, 87.3%; 65.3%; and 26.2%, respectively, attested they had never heard anything about it. It was also observed, from statistical analysis Chi-square test (p < 0.05), the variables schooling and age group can influence the knowledge about zoonoses and the veterinarian’s working areas. Based on the obtained results, it is evident the respondents precarious knowledge about diseases of great importance for public health and that rely on the veterinarian as an ally to strengthen the work of Basic Health Care.